(Un)timely Crises
XI, 101 p. 16 illus.
Keywords: “(Un)timely Crises offers new pathways for thinking ‘crisis,’ this catchword of our time. In critical and interdisciplinary fashion, the book mobilizes the chronotope to give innovative insights into various crisis typologies, geographies, and temporalities. Through theory and examples, the authors show how to refine our understandings of and our modes of learning from crises. The book is ideal for everyone seeking to rethink the concept of crisis and the practice of critique.” - Miriam Meissner, author of Narrating the Global Financial Crisis: Urban Imaginaries and the Politics of Myth (2017). “This book offers invaluable insights into the spatio-temporal effects of the rhetoric of crisis. Concise in format, it provides a wealth of reflection about the ‘grammars’ of crisis by scholars from various fields. It is a must for every scholar who wants to understand the complex ramifications of the use of the term‘crisis’ and an indispensable volume for these crisis-ridden times.” - Stijn De Cauwer, editor of Critical Theory at a Crossroads: Conversations on Resistance in Times of Crisis (2018). (Un)timely Crises explores how ‘crisis’—as a narrative, concept, grammar, and experience—structures time and space. This collectively written volume extends Bakhtin’s ‘chronotope’ to challenge mobilizations of crisis within neoliberal governmentality. The book explores how contemporary crises can trigger memories and traumas of earlier events as well as foster practices of resistance and alternative visions of the future. Drawing from across disciplines and geographical contexts, (Un)timely Crises reimagines the relation of ‘crisis’ with ‘critique’, proposing future trajectories for thinking and living in and through crisis.